2021
DOI: 10.30703/cije.704925
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Bakış Açılarıyla Okul Öncesi Eğitimde Kalite Unsurları: Nitel Bir Araştırma

Abstract: This paper was checked for plagiarism using iThenticate during the preview process and before publication. / Bu çalışma ön inceleme sürecinde ve yayımlanmadan önce iThenticate yazılımı ile taranmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…In the study of Karademir and Akman (2021), in which they aimed to determine the thoughts of teachers and institution administrators working in pre-schools about quality in early childhood education, it was revealed that quality was related to physical conditions and the quality of the teacher, the content of educational services, and the positive attitude habits desired to be given to children. In the research conducted by Karademir and Ören (2020), it has been concluded that the quality of education is affected by the physical environment and materials, as well as the proficiency of teachers, the number of children in the class, the number of children per teacher, the interaction of children with teachers, the education program, communication, the education of the family and the inclusion of the family in the process.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Karademir and Akman (2021), in which they aimed to determine the thoughts of teachers and institution administrators working in pre-schools about quality in early childhood education, it was revealed that quality was related to physical conditions and the quality of the teacher, the content of educational services, and the positive attitude habits desired to be given to children. In the research conducted by Karademir and Ören (2020), it has been concluded that the quality of education is affected by the physical environment and materials, as well as the proficiency of teachers, the number of children in the class, the number of children per teacher, the interaction of children with teachers, the education program, communication, the education of the family and the inclusion of the family in the process.…”
Section: Discussionmentioning
confidence: 99%
“…According to Derman and Kahraman (2012), the classroom mother is the person who supports the teacher in organizing the classroom, eliminating the deficiencies and meeting the needs, and communicating with the parents of the students. While there is a mother/sister/assistant in pre-school education to meet the needs and support the teacher, there are usually classroom mothers in primary school (Karademir & Akman, 2021). As can be understood from these statements, it is obvious that the classroom mother is of great importance.…”
Section: Problem Statusmentioning
confidence: 99%
“…Millî Eğitim Bakanlığının mevzuat ve yönetmeliklerinde varlığı resmen tanımlanmamış olsa da okul ikliminin paydaşlarından biri olarak sınıf annesi ya da sınıf anneliği kendini göstermektedir. Okul öncesi eğitimde, öğretmenle birlikte, genellikle kadrolu/ücretli bir sınıf annesi/ablası/yardımcısı olması son derece doğal iken, benzer ihtiyaçları ilkokulda veliler arasından seçilen sınıf annesi karşılamaktadır (Karademir ve Akman, 2021).…”
Section: Introductionunclassified